Enhancing Arabic Reading Comprehension Through the Reference Epistemological Model: Meningkatkan Pemahaman Membaca Bahasa Arab Melalui Model Epistemologis Referensi - Hikmah Maulani; Jenal Bustomi; Nalahuddin Saleh; Erni Haryanti; Supiana (ELOQUENCE : Journal of Foreign Language, 2025)
Background: Reading comprehension (qirā’ah) is a fundamental skill in learning Arabic as a foreign language. As the complexity of texts and the demands of critical literacy increase, there is a need for a conceptual model that can map the cognitive and epistemic processes involved in understanding Arabic texts. Purpose: This study explores the technical potential of the Reference Epistemological Model (REM) in enhancing students' qirā’ah comprehension. Method: This study employs a qualitative approach with an exploratory case study design. Data were collected through text-based comprehension tests using authentic materials, semi-structured interviews, structured observations, and classroom documentation. Thematic analysis results indicate that the REM is effective in identifying students’ conceptual representations, epistemic activities, and epistemic stances while reading Arabic texts. Results and Discussion: The main findings indicate that the majority of students are still at the stage of literal comprehension and have not yet fully activated inferential and reflective strategies in reading. The REM has potential as both a diagnostic and pedagogical framework for developing qirā’ah assessment, constructing authentic evaluation rubrics, and designing learning strategies based on deep meaning-making. Conclusions and Implications: Contains one to two important sentences. This section provides a conclusion about the results of the research and what these results mean for us today, as well as the implications of the suggested research results for future research on the topic.